State of the Art and Emerging Technologies in Vaccine Design for Respiratory Pathogens - Ridelfi, Matteo; Pierleoni, Giulio; Fonseca, Vittoria Zucconi Galli; Batani, Giampiero; Rappuoli, Rino; Sala, Claudia (Seminars in Respiratory and Critical Care Medicine, 2025)
In this review, we present the efforts made so far in developing effective solutions to prevent infections caused by seven major respiratory pathogens: influenza virus, respiratory syncytial virus (RSV), the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), Bordetella pertussis, Streptococcus pneumoniae (pneumococcus), Mycobacterium tuberculosis, and Pseudomonas aeruginosa. Advancements driven by the recent coronavirus disease 2019 (COVID-19) crisis have largely focused on viruses, but effective prophylactic solutions for bacterial pathogens are also needed, especially in light of the antimicrobial resistance (AMR) phenomenon. Here, we discuss various innovative key technologies that can help address this critical need, such as (a) the development of Lung-on-Chip ex vivo models to gain a better understanding of the pathogenesis process and the host–microbe interactions; (b) a more thorough investigation of the mechanisms behind mucosal immunity as the first line of defense against pathogens; (c) the identification of correlates of protection (CoPs) which, in conjunction with the Reverse Vaccinology 2.0 approach, can push a more rational and targeted design of vaccines. By focusing on these critical areas, we expect substantial progress in the development of new vaccines against respiratory bacterial pathogens, thereby enhancing global health protection in the framework of the increasingly concerning AMR emergence.
Keywords: vaccines; antimicrobial resistance; respiratory pathogens; immune system; infectious diseases